The Level of Depression and Anxiety among Caregivers of Patients with Schizophrenia - Mehmood, Nasir; Talib, Uroosa; Naeem, Farooq (British Journal of Healthcare and Medical Research, 2022)
Caregivers of patients with mental health problems experience many emotional problems like depression, anxiety, anger, shame and guilt. Incorporating the role of care into pre-existing roles, along with the stigma associated with mental illness, creates psychological and financial stress for caregivers. This study aims at assessing the level of depression and anxiety among caregivers of schizophrenic patients. It was a cross-sectional study. Participants (n = 65) were approached in in-patient and out-patient units of private hospitals. Depression and Anxiety were assessed through Hamilton Rating Scale for Depression and anxiety. Results were analyzed using SPSS. 24.6% of caregivers are in the moderate to the severe category while 38.5% of caregivers are in the mild category of anxiety on the Hamilton Anxiety Rating Scale. On Hamilton Rating Scale for Depression, 61.5% of caregivers were in the moderate to severe category of depression. Caregivers of patients with severe mental illness experience high level of depression and anxiety. Appropriate interventions should be targeted to improve the psychological well-being of caregivers.